Elaboración de un plan de marketing para la distribuidora de helados pingüino Cotopaxi durante el periodo 2013 -2017 - Bermeo Silva, Juan Sebastián (2015)
The purpose of this research is to implement a Marketing Plan in order to establish strategies, actions, and results as well as to improve the profitability of the company. It identifies aspects that generate malfunctioning in some processes by improving and automating procedures in a new administration. These actions have been achieved thanks to Mr. Fausto Hervas, in 37 years of existence of ‘PINGUINO’ ICE CREAM in our Province….